Highly photocatalytic performance of TiO2 nanowires in the conversion of benzaldehydes to benzoic acid - Sudirman Sudirman; Lalu Dimas Pratama Atmaja; Ari Jamhari Pratama; Emmy Yuanita; Ni Komang Tri Dharmayani; Maria Ulfa; Romel Hidayat (The University of Mataram, 2023)
The synthesis of environmentally friendly-based chemicals such as solvent-free continues to be developed. A critical precursor in chemical synthesis is benzoic acid. This research developed a synthesis method by utilizing TiO2 nanomaterials with different morphologies as photocatalysts, namely nanoparticles (NPs) and nanowires (NWs). Titanium (IV) oxide with nanowires morphology was synthesized by hydrothermal method under alkaline conditions. SEM, XRD, and FT-IR images confirmed the morphologies of TiO2 NPs and TiO2 NWs. Photocatalytic performance in converting benzaldehyde to benzoic acid showed a significant difference of up to 38% using TiO2 NPs and 94% using TiO2 NWs.